THE ROLE OF RELIGIOSITY AND ETHICS ON ISLAMIC BANK CONSUMERS’ BEHAVIOUR: A MAQASID SHARIAH PERSPECTIVE - Nuraziza Nuraziza; Suhardi M. Anwar; Muhammad Aqsa; Hadi Pajarianto, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research investigates how religiosity influences Muslim consumers' ethics, which subsequently affect Muslim consumers' attitude and commitment. The sample consists of 392 Muslim and bank consumers, obtained through a survey study using structural equation modeling (SEM) to test the research hypotheses. The empirical results indicate that religiosity has significant positive effects on consumers’ ethics. Furthermore, the mediator consumers’ ethics partially mediate religiosity and consumers’ religiosity on the outcome variables (e.g., consumers’ attitude and commitment). This study validated the religious beliefs of Indonesian Muslims, necessitating further research across various cultures and regions. This study can assist Islamic bank managers and scholars in observing the relationship between religion, Islamic bank products, and the level of commitment among Muslims. The current study sheds light on consumers' understanding of Islamic bank principles through marketing and religiosity. The government and the Shariah Supervisory Board (SSB) must strengthen their oversight and promotion efforts to ensure that Islamic banking operations align with Islamic law.